2007
DOI: 10.1002/lt.21308
|View full text |Cite
|
Sign up to set email alerts
|

Predicting immunosuppressant dosing in the early postoperative period with noninvasive indocyanine green elimination following orthotopic liver transplantation

Abstract: Twenty adult patients undergoing orthotopic liver transplantation (OLT) were enrolled in this study, with the noninvasive indocyanine green plasma disappearance rate (ICG-PDR) measured both during and after OLT to assess the relationship between ICG-PDR and the ability of patients to achieve therapeutic postoperative tacrolimus immunosuppressant blood levels. Liver function was determined at both 2 and 18 hours post reperfusion with the ICG-PDR k value (1/min). Postoperative standard serum measures of liver fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…1 Nevertheless, hepatic ischemia-reperfusion (IR) remains a major deleterious factor influencing graft outcome in organ transplantation. The incidence of primary graft failure (5% to 15%) and initial poor function (10% to 25%) is strongly dependent on the extent of ischemia-reperfusion injury (IRI).…”
mentioning
confidence: 99%
“…1 Nevertheless, hepatic ischemia-reperfusion (IR) remains a major deleterious factor influencing graft outcome in organ transplantation. The incidence of primary graft failure (5% to 15%) and initial poor function (10% to 25%) is strongly dependent on the extent of ischemia-reperfusion injury (IRI).…”
mentioning
confidence: 99%
“…The decrease noted between the third and fifth days post-transplantation was an early marker of acute cellular rejection, which developed earlier than the increase in liver enzymes. Parker et al 27 reported that they did not find any association between PDR-ICG values and postoperative liver biopsy when the PDR-ICG values were evaluated only 2 and 18 hours postreperfusion. The mean PDR-ICG values were within the normal range; this was the same as our results on days 1 and 2.…”
Section: Discussionmentioning
confidence: 98%
“…The decrease noted between the third and fifth days post‐transplantation was an early marker of acute cellular rejection, which developed earlier than the increase in liver enzymes. Parker et al27 reported that they did not find any association between PDR‐ICG values and postoperative liver biopsy when the PDR‐ICG values were evaluated only 2 and 18 hours post‐reperfusion. The mean PDR‐ICG values were within the normal range; this was the same as our results on days 1 and 2.…”
Section: Discussionmentioning
confidence: 99%